Analyses of mortality and prevalence of cerebrovascular disease in Colombia, South America (2014-2016): A cross-sectional and ecological study (2020)
Background: Stroke is the second cause of death and the first cause of disability worldwide. However, although numerous reports regarding stroke epidemiology in Latin America have been published, they differ widely in terms of employed methods and end points. This is the first of a series of articles that describes the epidemiology of stroke and other cerebrovascular diseases (CVD) in the nation, as well as their correlation with recognized risk factors and social variables. Methods: Descriptive analyses were performed using the Colombian vital registration system and social security information system as primary data sources. Rates and ratios were calculated, corrected for under-registration, and standardized. Secondary analyses were made using data from national surveys and government organizations on hypertension, diabetes mellitus, sedentarism, obesity, tobacco and alcohol consumption, and unsatisfied basic needs. Factorial multivariate multiple regression analyses were performed to evaluate correlations. Concentration curves and indices were calculated to evaluate for inequities in the distribution of events. Results: Global CVD had a national mortality rate and a prevalence ratio of 28 and 142 per 100,000 persons, respectively. Nontraumatic intracranial hemorrhage had the highest mortality rate (ie, 15 per 100,000), while cerebral infarction and transitory cerebral ischemia had the highest prevalence ratios (ie, 28 and 29 per 100,000, respectively). Hypertension and tobacco use were the most relevant risk factors for most of the simple and multiple models, and cerebral amyloid angiopathy and nonpyogenous intracranial venous thrombosis were the disease categories with the most socially unequal distribution of deaths and cases (ie, concentration indices of .34 and .29, respectively). Conclusions: CVDs are a cause for concern in Colombia and a marker of healthcare inequality and social vulnerability. Nationwide control of risk factors such as hypertension and tobacco use, as well as the design and conduct of public policy focused on the vulnerable and medically underserved regions and on standardizing mandatory CVD registries might ease its burden.